PERCEPTIVE CHANGES IN ENDURANCE ATHLETES DURING SOCIAL ISOLATION DUE TO COVID-19 - Guilherme,Flávio Ricardo (2020)
ABSTRACT Introduction: The COVID-19 pandemic has led to social isolation measures in different contexts. In endurance sports, competitions worldwide have been canceled, affecting behavioral, psychological, and physical aspects. Objective: This study aimed to assess potential associations between stress, motivation, behavioral changes, and physical fitness in endurance athletes, and time in social isolation. Methods: A cross-sectional study with the participation of 201 athletes, including mountain bikers (n = 89), runners (n = 88) and triathletes (n = 24). Each participant answered questions about time spent in isolation; body weight; changes in training schedule during the isolation period; levels of motivation; stress levels; loss of physical fitness; what aspect of physical fitness was most jeopardized during the isolation period; alcohol consumption; quality of sleep; quality of diet; and whether they had been ill during the isolation period. Results: The results showed significant differences between the percentage of runners (4.5%) and triathletes (16.7%) who had been isolated from 1-10 days, and between the percentage of cyclists (41.6%) and runners (68.2%) in 11-20 days and >20 days (28.1% and 9.1%) respectively. Social isolation was significantly associated with at least one variable for the three groups of athletes; however, the runners were the most affected by the pandemic, presenting an association with low motivation, high stress, poorer quality of sleep, increased alcohol consumption, and loss of physical fitness. Conclusion: Our study showed that the period of social isolation, specifically over time > 10 days, generated significant changes in the perceptions of motivation, stress, alcohol consumption, and physical fitness of endurance athletes, with runners being the most affected group. Level of Evidence III; Diagnostic studies - Investigation of a diagnostic test; Study of non-consecutive patients, without a “gold standard” applied uniformly.